Analisis Manajemen Risiko Bank Syariah Dalam Melakukan Transformasi Digital (Studi Kasus Pada Bank AS) - Abdul Malik Fajri; Evony Silvino Violita (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to find out how appropriate the application of risk management is in carrying out digital transformation at Bank AS in accordance with the applicable provisions and concepts, so that it can be used as material for consideration for management to make improvements and strengthen the application of risk management, especially in carrying out the digitalization process in Islamic banking. This research uses a qualitative approach in the form of case study research. The data used is primary data with research data collection instruments in the form of interviews and secondary data in the form of documentation. The object of research is the Bank AS, which is one of the sharia banks that is currently carrying out digital transformation of its services. The results of the study show that Bank AS already has the implementation of risk management related to information technology in carrying out digital transformation which is in line with the three components of the Risk IT Framework however, there are several things that are considered to be obstacles such as in socializing a culture of risk awareness, delays in reporting, and regarding plans mitigation.